Literature of Review Analysis of Place Selection Strategy Based on Comfortable, Clean Environment, Responsiveness of Service on Product Purchasing Decisions at Coffee Shop Fore - Putri Salsabilla Rahmawati (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
The convenience factor is an important combinationof many different factors that influence thecustomer's purchasing decision process. Thecleanliness factor also has a very big influencebecause customers everywhere have the same desirewhere to get their needs, especially food, the placemust be really clean, healthy and free from germs.The population in the study was all Fore coffee shopconsumers throughout Indonesia, while sampling inthis study used side accidental techniques. Datacollection techniques in research use observation anda list of questions. Data analysis techniques used inthis research include validity testing, reliabilitytesting, classical assumption testing, and multiplelinear regression analysis with the help of SPSS ForWindows 22 software